RESPON PERTUMBUHAN BIBIT SUKUN (Artocarpus communis Forst) PADA PEMBERIAN KOMPOSISI PUPUK KANDANG DAN KOMPOSISI TANAH YANG BERBEDA - Vardos Ricky Doddy Silalahi; Budi Utomo; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2015)
Breadfruit plants (Artocarpus communis Forst) had significant importance in supporting the needs of the food source because it can support crop diversification efforts that serve as the non-rice food reserves. In connection with this, to rehabilitate in an area where rainfall is done with a bit of fertilizer that can hold water so it is more resistant to drought situation and breadfruit which incidentally is a plant that is able to live in dry conditions so it will be obtained an effective condition for application of fertilizers in the rehabilitation of degraded land, especially in drought conditions. This study aims to determine the ability of manure in retaining water and nutrient supply to the breadfruit plants. Manure with different doses will affect the binding of water and growing resistance breadfruit seeds. This study used a completely randomized design (CRD) non factorial consisting of one treatment with four replicates with different doses of fertilizer. If ANOVA table is significant then proceed with further tests based on real distance test DMRT (Duncan's Multiple Range Test). Provision of multiple doses of chicken manure on breadfruit seeds significantly affected as height but did not significantly affect the increase in diameter. The highest breadfruit seeds survival skills at P8, while the lowest is in P0.Keyword : Artocarpus communis. Forst, Manure, Degraded Land